Etnografi Virtual dalam Jurnalisme Digital: Studi Kasus Akun Medantalk dalam Membentuk Narasi Lokal di Media Sosial - Shila, Nadia Frety; Kharisma, Citra Puja; Chairina, Chairina (Lembaga Intelektual Muda Maluku, 2024)
Virtual ethnography is an approach in social research to understand human interaction in the digital world. This study uses a qualitative method with a virtual ethnography approach to analyze how the MedanTalk account shapes local narratives through the dissemination of information on social media. Data were collected through content analysis and interviews with active users of the MedanTalk account. The data analysis technique used was thematic analysis, which aims to identify patterns in the presentation of information and user responses to the issues raised. The results of the study show that the MedanTalk account plays an important role in shaping the perception of the Medan community regarding local issues, especially in the context of disaster information, security, and local cultural promotion.